2019
DOI: 10.1038/s41467-019-12234-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of cellular addiction to DNA polymerase theta

Abstract: Polymerase theta (Pol θ, gene name Polq) is a widely conserved DNA polymerase that mediates a microhomology-mediated, error-prone, double strand break (DSB) repair pathway, referred to as Theta Mediated End Joining (TMEJ). Cells with homologous recombination deficiency are reliant on TMEJ for DSB repair. It is unknown whether deficiencies in other components of the DNA damage response (DDR) also result in Pol θ addiction. Here we use a CRISPR genetic screen to uncover 140 Polq synthetic lethal (PolqSL) genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
128
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 131 publications
(150 citation statements)
references
References 65 publications
6
128
0
1
Order By: Relevance
“…Fig. 4A) – the most frequent Pol θ-dependent repair products for a given chromosome break, and serve as a biomarker for TMEJ activity (Feng et al ., 2019). However, some MHD are favored during NHEJ (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fig. 4A) – the most frequent Pol θ-dependent repair products for a given chromosome break, and serve as a biomarker for TMEJ activity (Feng et al ., 2019). However, some MHD are favored during NHEJ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Past work from our group and others has determined that in some contexts, Pol θ-dependent repair can include microhomologies more distal than 15 bp from 3’ termini. These contexts include cells deficient in regulation of end resection (cells defective in KU or 53BP1 ) or wild type cells after a much longer recovery period than is used here (24 hours) (Wyatt et al ., 2016; Schimmel et al ., 2017; Feng et al ., 2019). Given our results with pre-resected substrates, we suggest this second class of Pol θ-dependent products reflects loss of 3’ terminal ssDNA before Pol θ could be engaged, rather than a fundamental change in the preference of Pol θ for break proximal microhomologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have demonstrated that cells with NHEJ deficiency exhibit a compensatory increase in alternative end-joining repair mediated by DNA polymerase theta (Pol θ, gene POLQ ) 4,33,34 . Polymerase theta dependent end joining (TMEJ) of DNA DSBs is characterized by deletions and templated insertions that are flanked by short tracts of sequence identity, or microhomology (MH) 4 .…”
Section: Resultsmentioning
confidence: 99%